Diffuse midline glioma-H3K27M mutant. A novel entity with a defining and specific IHC marker - Prachi Agarwal; Hema Malini Aiyer (Wolters Kluwer Medknow Publications, 2021)
Diffuse Midline Glioma-H3K27M mutant is a specific entity added to the 2016 updated WHO classification of CNS tumours that represents the majority of diffuse intrinsic pontine gliomas, although identical tumours are also found elsewhere in the midline. They are aggressive tumours with a poor prognosis and considered WHO GRADE IV regardless of histological features.[1],[2] Patients with H3K27M-mutant gliomas in unusual anatomical locations have a better prognosis than those with corresponding tumors in the brainstem and this helps in the treatment stratification of diffuse gliomas. Extrapolating from the clinicopathologic features of diffuse pontine gliomas and the poor prognosis seen in pediatric diffuse midline gliomas with H3 K27M mutations, the presence of an H3 K27M mutation in an infiltrating astrocytoma of the midline automatically confers a grade IV status.[2],[3] This case emphasizes the need for Immunohistochemistry using a mutation-specific H3K27M antibody in all cases of midline gliomas.